Influence of Storage Period on the Geochemical Evolution of a Compressed Energy Storage System - Iloejesi, Chidera O.; Beckingham, Lauren E. (Frontiers in Water, 2021)
Subsurface porous aquifers are being considered for use as reservoirs for compressed energy storage of renewable energy. In these systems, a gas is injected during times in which production exceeds demand and extracted for energy generation during periods of peak demand or scarcity in production. Current operational subsurface energy facilities use salt caverns for storage and air as the working gas. CO2 is potentially a more favorable choice of working gas where under storage conditions CO2 has high compressibility which can improve operational efficiency. However, the interaction of CO2 and brine at the boundary of the storage zone can produce a chemically active fluid which can result in mineral dissolution and precipitation reactions and alter the properties of the storage zone. This study seeks to understand the geochemical implications of utilization of CO2 as a working gas during injection, storage and extraction flow cycles. Here, reactive transport simulations are developed based on 7 hours of injection, 11 hours of withdrawal and 6 hours of reservoir closure, corresponding to the schedule of the Pittsfield field test, for 15 years of operational life span to assess the geochemical evolution of the reservoir. The evolution in the storage system is compared to a continuously cyclic system of 12 hours injection and extraction. The result of the study on operational schedule shows that mineral reactivity occurs at the inlet of the domain. Furthermore, the porosity of the inner domain is preserved during the cycling of CO2 acidified brine for both systems.